Prognostic Impact of Platelet-Large Cell Ratio In Myelodysplastic Syndromes - Chen, Qiuni; Chen, Yue; Zhang, Yijing; Zhang, Lijuan; Chen, Kankan; He, Zhengmei; Wang, Chunling; Yu, Liang (Frontiers in Oncology, 2022)
Background Myelodysplastic syndromes (MDSs) are a very heterogeneous group of myeloid disorders with high prevalence and risk of developing acute myeloid leukemia. The more accurate risk stratification can provide a better guidance of treatment. The platelet–large cell ratio (P-LCR) is a parameter reported in complete blood cell count tests, and was associated with many diseases, but its role in MDS is not clear. Purpose This study aims to explore the impact of the P-LCR on the prognosis of patients with MDS, which is of great significance for clinical treatment. Methods In the retrospective study, 122 newly diagnosed MDS patients were enrolled. We used the bioinformatics tool X-tile to define a P-LCR threshold of 36.7% to predict prognosis. Patients were divided into P-LCRlow and P-LCRhigh groups, and their characteristics were compared between the two groups. Results Results show that the P-LCRlow was associated with worse overall survival (OS) than the P-LCRhigh patients (median OS, 18.53 months versus 25.77 months, p=0.0057), but there were no statistical differences in progression-free survival (PFS) between the two groups (p=0.2001). The results of univariate and multivariate Cox proportional hazard analyses adjusted for gender, bone marrow blast level, platelet count, and International Prognostic Scoring System scores showed that the P-LCR was useful in the evaluation of PFS [hazard ratio (HR) 0.212, 95%CI 0.064–0.702, p=0.011] and OS of MDS (HR 0.464, 95%CI 0.284–0.757, p=0.002). Conclusion This study is the first report showing that the P-LCR would be a simple and immediately available biomarker for predicting the prognosis of MDS.